Carotid angiography - Arne Torkildsen (Arquivos de Neuro-Psiquiatria)
After a brief review of the history of cerebral angiography, some of the most important points concerning the percutaneous angiographic technique have been described. The value of the angiographic examination in cases of cerebral gliomas has been studied, based upon a consecutive series of 127 verified cases of hemispherical gliomas. Of 31 cases of frontal glioma, 28 could be diagnosed by the angiographic method; of 33 cases of parietal glioma, the angiograms revealed the neoplasm in 27 instances; of 39 cases of temporal glioma, the tumor could be localized in 38 cases; of 13 cases of occipital glioma, the angiographic localization of the tumor was successfull in 9 instances; of 11. cases of glioma infiltrating the corpus callosum and (or) the basal ganglia, the angiographic examination was successful in only 3 cases. The angiographic examination in cases of cerebral glioma, in my experience, yields a more satisfactory result as to the localization than does the pneumography. The only exception concerns the gliomas growing in the thalamus or in the basal ganglia. These are more easily localized by means of ventriculography. As to the differential diagnosis of the gliomas, tumor vessels could, be seen both in astrocytomas and in glioblastomas. Most cases of astrocytomas were however devoid of specific tumor vessels. When present they could not be definitely distinguished from those seen in glioblastomas, but the abnormal findings were far less numerous and definitely less pronounced in astrocytomas than in glioblastomas. In most cases the astrocytomas were characterized only by displacement of blood vessels of normal appearance, while the glioblastomas frequently-presented both displacement of normal appearing blood vessels and new formed blood vessels within the neoplasm itself. The pathological blood vessels in the tumor were frequently abnormal both regarding their topographical appearance and their type. Frequent findings were arterio-venous aneurysms, sudden variation of the caliber, parallel arrangement of the small tumor vesesls and fields of hypervascularization. In 37 of 55 cases of glioblastoma such vascular changes indicated the differentia) nature of the neoplasm.